Investigation on Piezoelectric Output Property of Bi2.5Na3.5Nb5O18 Modified P(VDF-TrFE) Piezoelectric Composite Films with Hierarchical Layer Structure - Luo, Jun (Langmuir : the ACS journal of surfaces and colloids, 2025)
In this study, Bi2.5Na2.5Nb5O18 (BNN5)/poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) piezoelectric composite films were prepared via electrospinning technology. Meanwhile, the uniaxial intermittent alternating dual-spray method was employed to obtain composite films with alternating concentration variations of BNN5, which were then utilized to fabricate piezoelectric nanogenerators (PENGs). Among them, the composite film with a BNN5 content of 3/5 wt % exhibited the optimal β-phase proportion, reaching 85.1%. The piezoelectric output performance of this composite film was significantly enhanced: it had an output voltage as high as 25.3 V, which was 339.2% higher than that of the P(VDF-TrFE) film and 54.7% higher than that of the 4 wt % composite film with the same concentration. When the resistive load was 1 MΩ, the peak instantaneous output power was 38.3 μW, with a calculated current of 6.2 μA and an output power density of 5.1 μW/cm2. Both the current and power were higher than those of most reported PVDF/P(VDF-TrFE)-based piezoelectric films. The durability test with over 2200 cycles demonstrated that the piezoelectric composite film had excellent mechanical stability. This work presents a strategy to boost the output performance of piezoelectric composite films, namely, fabricating P(VDF-TrFE) composite films using the uniaxial intermittent alternating dual-spray technique, to meet the requirements of wearable and flexible electronic devices